EXPERIMENTAL STUDY OF PACK CARBURIZING AND QUENCHING PROCESS WITH TEMPERATURE VARIATIONS (700℃, 800℃, AND 900℃) ON THE MICRO-CHARACTERISTICS AND HARDNESS OF STAINLESS STEEL 316L - Daniel Angger; Bernardus Crisanto Putra Mbulu; Antonius Prisma Jalu Permana (Universitas Katolik Widya Karya Malang, 2025)
His study aims to investigate the effect of temperature variation in pack carburizing and quenching processes on the microstructure and surface hardness of Stainless Steel 316L. The pack carburizing process was conducted using activated carbon derived from robusta coffee grounds at temperatures of 700°C, 800°C, and 900°C with a holding time of 60 minutes. Subsequently, a quenching process was carried out using oil mixed with activated carbon to lock the diffused carbon. The material was tested for mass change, microstructure (via SEM), and surface hardness (using the Vickers method). The results show that increasing temperature significantly affects carbon diffusion and hardness improvement. The highest hardness value was obtained from the quenching process at 900°C with 330 HV, while pack carburizing at the same temperature resulted in 292 HV. The microstructure revealed more dominant Martensitic formation in the quenching process. Therefore, heat treatment with rapid cooling proves to be more effective in enhancing hardness and modifying the microstructure of Stainless Steel 316L.